Femtosecond laser-assisted implantation of complete versus incomplete rings for keratoconus treatment - Hosny M (Dove Medical Press, 2015)
Mohamed Hosny, Esraa El–Mayah, Mohamed Karim Sidky, Mohamed Anis Department of Ophthalmology, Cairo University, Giza, Egypt Purpose: To compare complete versus incomplete ring implantation for keratoconus correction.Methods: We investigated 25 eyes of keratoconic patients, of which 15 had femtosecond-assisted MyoRing corneal implantation (Group 1) and 10 had femtosecond-assisted Keraring segments (Group 2). Uncorrected distance visual acuity (UCVA), best corrected distance visual acuity (BCVA), mean K (Km), sphere, topographic cylinder, and corneal asphericity value (Q-value) were measured in all eyes preoperatively and at 4 weeks postoperatively (1 month).Results: In Group 1, the Km change was -6.15±2.16 D, with a mean change in sphere of 4.45±2.18 D and a mean change in refractive cylinder of 2.32±3 D. UCVA change was -0.57±0.273 logarithm of the minimum angle of resolution (LogMAR), BCVA change was -0.2±0.27 (LogMAR), and the Q-value change was 0.43±2.6. In Group 2, the Km change was -3.15±1.68 D, UCVA change was -0.48±0.37 (LogMAR), BCVA change was -0.09±0.15 (LogMAR), and the Q-value change was 0.5±0.21. Changes in the means did not significantly differ between groups, except for the Km change, which was significantly greater in Group 1 than in Group 2 (P=0.05).Conclusion: Both complete ring and ring segment implantation are effective for improving corneal and visual parameters in keratoconus. Complete ring implantation may have a greater flattening effect on the anterior corneal surface. Keywords: KeraRing, MyoRing, keratoconus, femtosecond